The marine biology of law and human health. (29th June 2015) - Appleby, Thomas; Kinsey, Susan; Wheeler, Benedict; Cunningham, Emma
Abstract : This review uses a multidisciplinary approach to investigate legal issues concerning the oceans and human health. It firstly seeks to define the boundaries of oceans and human health research. We use three case studies as examples: biomedical research, marine litter and human well-being. Biomedical research raises complex issues relating to coastal states' sovereign rights to exploit their marine resources and the patenting processes. Coastal states have differing degrees of control over research at sea. There are differences in EU and US law over the status of genetic discoveries, with the US having stricter criteria to qualify for patent protection. International law sets the standard for bioprospecting in developing countries under the Nagoya Protocol. The cost and complexity of marine biomedical research mean that it cannot be left to commercial exploration and needs some public funding. The second case study highlights the rise in marine plastics pollution using Marine Conservation Society beachwatch data. It details the need to alter product design to avoid marine pollution and records an unsuccessful attempt by academics and an NGO to make contact with the manufacturers of one polluting product. It also introduces the concept that faulty design could amount to a public nuisance. The third case study highlights the potential health benefits from access to the coast and the statutory responsibility which sits with the US and UK authorities in the provision of well-being. It posits that there needs to be greater inter-agency coordination to promote access to the coast for human well-being.